The expression of quantity in Oneida: a study in syntactic and semantic variation - Koenig Jean-Pierre; Michelson Karin (Linguistic Typology)
One of the questions linguists try to answer is to what extent conceptual content is expressed similarly across languages. The null hypothesis is that languages express the same sorts of things but may differ in the particular morphological and syntactic constructions they use. This paper describes one semantic domain, quantification over objects in Oneida (Northern Iroquoian), where there is both variation in expression and variation in expressibility. Through a detailed and comprehensive description of quantificational expressions, we show that in Oneida quantification is pervasively and almost exclusively expressed by productive verb forms that are not number words; moreover, these verb forms head clauses (count clauses) adjoined to main clauses. We argue that to this morphosyntactic difference between Oneida and most languages corresponds a semantic difference, namely that in Oneida quantificational expressions denote properties of sets, whereas in most other languages they denote relations between sets (or between entities and sets), and this difference accounts for the systematic absence of proportional and partitive quantifiers in Oneida.